Antibodies to Xenopus egg S6 kinase II recognize S6 kinase from progesterone- and insulin-stimulated Xenopus oocytes and from proliferating chicken embryo fibroblasts. - Erikson, E (1987)
Ribosomal protein S6 becomes highly phosphorylated during progesterone- or insulin-induced maturation of Xenopus laevis oocytes. We have previously purified an Mr 92,000 protein as one of the major S6 kinases from Xenopus unfertilized eggs. In this paper we confirm by renaturation of activity from a sodium dodecyl sulfate-polyacrylamide gel that this protein is an S6 kinase. This enzyme, termed S6 kinase II (S6 K II), was used for the preparation of polyclonal antiserum. Immunocomplexes formed with the antiserum and purified S6 K II were able to express kinase activity with the same substrate specificity as that of the purified enzyme, including autophosphorylation of S6 K II itself. The antiserum did not react with S6 kinase I, another major S6 kinase present in Xenopus eggs, which is chromatographically distinct from S6 K II. The administration of progesterone to oocytes resulted in a 20- to 25-fold increase in S6 kinase activity in extracts of these cells. Immunocomplex kinase assays done on extracts revealed that anti-S6 K II serum reacted with S6 kinase from progesterone-treated oocytes. This antiserum also reacted with the activated S6 kinase from insulin-stimulated oocytes. In addition, anti-S6 K II serum reacted with activated S6 kinase from chicken embryo fibroblasts stimulated with serum or transformed by Rous sarcoma virus. These results indicate that S6 K II or an antigenically related S6 kinase(s) is subject to regulation by mitogenic stimuli in various cell types.